2004
DOI: 10.1096/fj.04-1890fje
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine gated electron transfer is key to the toxic mechanism of Alzheimer's disease β‐amyloid

Abstract: Alzheimer's disease (AD) is characterized by the presence of neurofibrillary tangles and amyloid plaques, which are abnormal protein deposits. The major constituent of the plaques is the neurotoxic beta-amyloid peptide (Abeta); the genetics of familial AD support a direct role for this peptide in AD. Abeta neurotoxicity is linked to hydrogen peroxide formation. Abeta coordinates the redox active transition metals, copper and iron, to catalytically generate reactive oxygen species. The chemical mechanism underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
301
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 253 publications
(319 citation statements)
references
References 41 publications
11
301
5
Order By: Relevance
“…Lyophilized Aβ40 and Aβ42 of greater than 95% purity were obtained from American Peptide (Sunnyvale, CA) or rPeptide (Athens, GA). H13A and H14A variants of Aβ42 were obtained from rPeptide, while Aβ 1-28 , Aβ [22][23][24][25][26][27][28][29][30][31][32][33][34][35] , α-MSH, and neurotensin were obtained from American Peptide. The Aβ42 mutant M35V (21) as well as Aβ42 with an oxidized methionine (M35 OX ) (20) were kindly provided by Dr. Kevin Barnham.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lyophilized Aβ40 and Aβ42 of greater than 95% purity were obtained from American Peptide (Sunnyvale, CA) or rPeptide (Athens, GA). H13A and H14A variants of Aβ42 were obtained from rPeptide, while Aβ 1-28 , Aβ [22][23][24][25][26][27][28][29][30][31][32][33][34][35] , α-MSH, and neurotensin were obtained from American Peptide. The Aβ42 mutant M35V (21) as well as Aβ42 with an oxidized methionine (M35 OX ) (20) were kindly provided by Dr. Kevin Barnham.…”
Section: Methodsmentioning
confidence: 99%
“…When DA was used as the oxidizable substrate instead of SAPC, it was also oxidized extensively by Cu(II) and H 2 O 2 over 120 min ( Figure 4C). Aβ42, Aβ 1-28 , and Aβ [22][23][24][25][26][27][28][29][30][31][32][33][34][35] inhibited DA oxidation but not the control peptides α-MSH and neurotensin. We conclude that Aβ peptides specifically inhibit oxidation of substrates such as SAPC and DA under these conditions.…”
Section: Antioxidant Activity Of Aβ42mentioning
confidence: 99%
“…PBT2 is a secondgeneration 8-OH quinoline, which, unlike its predecessor clioquinol, lacks iodine and was selected for clinical development because of its easier chemical synthesis, higher solubility, and increased blood-brain barrier permeability. Its clinical application was developed based on the potential to inhibit A␤ toxicity through modulation of A␤-metal interactions (13)(14)(15)(16), but the in vivo mechanism of action for PBT2 still requires elucidation. Cell culture studies have provided mechanism of action data to show that membrane-permeable compounds with the potential to form metal complexes, such as PBT2, can inhibit A␤ toxicity by increasing cellular metal ion bioavailability and activating neuroprotective cell signaling pathways (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The reduced Cu + ion prefers a trigonal coordination comprising the His residues. Previously it was demonstrated how the reduction of ACu 2+ involves the protonation and departure of Tyr10 from the first coordination shell around the copper ion [9]. We reasoned that for the reduction to be energetically favorable Tyr10 either does not bind to the metal or it must depart from it in an uncharged form prior to metal ion reduction.…”
Section: Met35 Radical Cation Formation Drives the Reduction Of Cu(ii)mentioning
confidence: 96%
“…In vitro it has been shown that the A copper complex (A/Cu) catalyzes the formation of hydrogen peroxide (H 2 O 2 ) from dioxygen (O 2 ) and substrates, such as ascorbic acid and cholesterol [7], which has been suggested to be one route to the oxidative stress observed in AD [8]. Both Tyr10 and Met35 have been demonstrated to be of pivotal importance for the redox-chemistry of A-Cu [9,10].…”
Section: Introductionmentioning
confidence: 99%